2016
DOI: 10.1038/srep22806
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial associations reveal spatial population dynamics in Anopheles gambiae mosquitoes

Abstract: The intolerable burden of malaria has for too long plagued humanity and the prospect of eradicating malaria is an optimistic, but reachable, target in the 21 st century. However, extensive knowledge is needed about the spatial structure of mosquito populations in order to develop effective interventions against malaria transmission. We hypothesized that the microbiota associated with a mosquito reflects acquisition of bacteria in different environments. By analyzing the whole-body bacterial flora of An. gambia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
101
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 35 publications
12
101
0
Order By: Relevance
“…This result is in accordance with previous reports that rather showed the influence of the local environment of the sampling site, environment that gives a specific bacterial profile to mosquito specimens (Boissière et al, 2012; Manguin et al, 2013; Buck et al, 2016). The microbiota diversity of host species will also be significantly influenced by the origin of specimens like wild versus laboratory reared Anopheles mosquitoes (Chavshin et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is in accordance with previous reports that rather showed the influence of the local environment of the sampling site, environment that gives a specific bacterial profile to mosquito specimens (Boissière et al, 2012; Manguin et al, 2013; Buck et al, 2016). The microbiota diversity of host species will also be significantly influenced by the origin of specimens like wild versus laboratory reared Anopheles mosquitoes (Chavshin et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The influence of the Anopheles microbiota on its vectorial competence to transmit pathogens is a growing field of investigation as demonstrated by the recent increase in studies, to cite a few (Favia et al, 2007; Briones et al, 2008; Dong et al, 2009; Rodrigues et al, 2010; Cirimotich et al, 2011; Blumberg et al, 2013; Gendrin and Christophides, 2013; Dennison et al, 2014; Buck et al, 2016). A previous report on the biodiversity of the abdomen microbiota of 100 wild Anopheles specimens (five species) from Dak Nong Province showed a high taxonomic diversity, including species reported as implicated in the mosquito resistance to Plasmodium infection (Ngo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent similar methods using 16S rRNA amplicon sequencing to determine the overall microbiota in wild mosquito populations has provided evidence for Wolbachia infections in An. gambiae in additional villages in Burkina Faso 71 and Anopheles species collected in Illinois, USA 72 . Our study describing resident Wolbachia strains in numerous species of Anopheles malaria vectors also highlights the potential for Wolbachia to be influencing malaria transmission, as postulated by previous studies 39, 40, 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Different ecological characters may have a significant impact on sand flies and their associated microbes. It has been shown that the acquisition of mosquito microbiota is associated with the eco-environment where mosquitoes inhabit30. Therefore, it is reasonable to speculate that the different microbial structure between the two sand fly samples from Henan and Sichuan may result from the interactions of the sand flies and their habitats.…”
Section: Discussionmentioning
confidence: 99%